Sleeping beauty? A prospective study on the prevalence of sleep problems and their potential determinants in professional dancers - Junge, A.; van Rijn, R. M.; Stubbe, J. H.; Hauschild, A. (Sports Medicine - Open, 2024)
Background Sleep is important for health and performance but has rarely been studied in professional dancers. The aim was to analyse the prevalence of sleep problems in professional dancers and their potential determinants at the beginning of and during the season.